International Migrations and Local Governance A Global Perspective (Migration, Diasporas and Citizenship,, 2018)
This volume provides a comprehensive overview of the role of local governments around the world in the management of the migration, integration and development nexus. Drawing on case studies from the Global North and South, this comparative work fills a lacuna in the existing literature which has focused largely on migration as addressed by European and North American cities. Further, it widens the current debate by confronting northern experiences with attitudes and strategies observed in sending countries; clearly demonstrating that international mobility has become a global issue for cities at both end of the migration spectrum. This innovative work will provide a valuable resource for students and scholars working in the social sciences, public policy and development; in addition to practitioners and policymakers.